A clinical decision framework to guide the outpatient treatment of emergency department patients diagnosed with acute pulmonary embolism or deep vein thrombosis: Results from a multidisciplinary consensus panel - Christopher Kabrhel; David R. Vinson; Alice Marina Mitchell; Rachel P. Rosovsky; Anna Marie Chang; Jackeline Hernandez‐Nino; Stephen J. Wolf (Journal of the American College of Emergency Physicians Open)
Abstract The outpatient treatment of select emergency department patients with acute pulmonary embolism (PE) or deep vein thrombosis (DVT) has been shown to be safe, cost effective and associated with high patient satisfaction. Despite this, outpatient PE and DVT treatment remains uncommon. To address this, the American College of Emergency Physicians assembled a multidisciplinary team of content experts to provide evidence‐based recommendations and practical advice to help clinicians safely treat patients with low‐risk PE and DVT without hospitalization. The emergency clinician must stratify the patient's risk of clinical decompensation due to their PE or DVT as well as their risk of bleeding due to anticoagulation. The clinician must also select and start an anticoagulant and ensure that the patient has access to the medication in a timely manner. Reliable follow‐up is critical, and the patient must also be educated about signs or symptoms that should prompt a return to the emergency department. To facilitate access to these recommendations, the consensus panel also created 2 web‐based “point‐of‐care tools.”